Effect of Crystalline Microstructure Evolution on Thermoelectric Performance of PEDOT : PSS Films - Xuan Huang; Liang Deng; Fusheng Liu; Qichun Zhang; Guangming Chen (Energy Material Advances, 2021)
Although organic polymer thermoelectric (TE) materials have witnessed explosive advances in the recent decade, the molecular mechanism of crystallization engineering of TE performance, even for the most successful polymer of poly(3,4-ethylenedioxythiophene) : poly(styrene sulfonate) (PEDOT : PSS), is still far from clear. Here, we deepen the understanding of the role of annealing-induced crystalline microstructure evolution on TE performance of the PEDOT : PSS film with thickness of 10 μm, which is usually more effective than thin ones in applications. Annealed at optimized temperature of 220°C, the film displays a power factor of 162.5 times of that of the pristine film before annealing. The enhanced TE performance is associated with the changes of crystallographic and morphologic microstructures, including increased crystallinity and crystal grain size, a domain morphology transformation from granular to crystalline nanofibril, and reduced insulating PSS in the skin layer. These variances facilitate the carrier transport by a transition from 3D to 1D hopping, reduce the activation energy, and improve the carrier mobility. The mechanism of crystallization engineering reported here can be conceptually extended to other TE polymers and guides the future rational design of preparation principles for organic and composite TE materials.